Pengaruh Penambahan Tepung Wortel Terhadap Kualitas Biskuit - Jublina Bakoil (Peneliti.net, 2022)
Carrot tubers contain nutrients needed by the body, especially vitamins and minerals, so this vegetable is very good and highly recommended to be consumed in the daily menu to meet the needs of vitamins and minerals that are essential for the body. Carrot flour is one of the processed products of fresh carrots and is a semi-finished ingredient. The results of research conducted by Deviurianty in Singal (2011) reported that carrot flour has a long shelf life of 6-8 months with a moisture content of <8%, so that carrot flour will be durable and widely used as food. The method used was a completely randomized design (CRD) with 4 (four) treatments and 3 (three) replications in order to obtain 12 (twelve) experimental units. There is a very significant effect of adding carrot flour to biscuits in terms of color, taste, and texture. The addition of carrot flour has a very significant effect on the color, taste, and texture. Treatment A (300 grams of carrot flour), was the best treatment, with the panelists' preference for texture 10.20, color 3.40 and taste 8.95.